A review of the impact of shift work on occupational cancer: Part 2 – mechanistic and health and safety evidence. Issue 1 (2nd January 2018) - Crawford, J. O.; Cherrie, J. W.; Davis, A.; Dixon, K.; Alexander, C.; Cowie, H.; McElvenny, D. M.
Abstract: The aim of this study is to carry out a review of the putative mechanism and health and safety evidence between 2005 and 2015 to inform practice using a systematic review methodology. The International Agency for Research on Cancer highlighted two potentially important mechanisms that may be involved in causing breast cancer following (night) shift work; light at night suppressing melatonin production and epigenetic changes in genes controlling circadian rhythms. Other mechanisms that have been investigated include the effect of chronotype, vitamin D status, psychological stress, fatigue, physiological dysfunction and poor health behaviours including smoking, drinking alcohol, poor diet, the timing of eating food and obesity. Interventions that have been investigated include shift design, pharmacological, chronotype selection, strategic napping and adherence to national cancer screening programmes. Suppression of night time production of melatonin and/or obesity remains the most plausible biological mechanisms for an association between shift work and cancer. Employers should facilitate the overall reduction in cancer risk for shift workers by enabling better health behaviours and facilitate access to national cancer screening programmes.